A possible synergistic effect of MTHFR C677T polymorphism on homocysteine level variations increased risk for ischemic stroke. Issue 51 (December 2017) - Li, Aifan; Shi, Yunshu; Xu, Liyan; Zhang, Yuchao; Zhao, Huiling; Li, Qiangmin; Zhao, Xingjuan; Cao, Xinhui; Zheng, Hong; He, Ying
Abstract: Background: Homocysteine (Hcy) plays an important role in vascular function and Hcy level contributes to pathogenesis of ischemic stroke (IS). MTHFR gene polymorphism may have effects on IS risks by influencing the Hcy metabolic pathway. In the present study, a case–control study was designed to evaluate the relationship among MTHFR C677Tpolymorphism, plasma Hcy level, and susceptibility of IS in Chinese population. Methods: A total of 300 patients with IS and 261 matched control subjects were recruited. Plasma Hcy concentration was determined using enzymatic cycling assay. MTHFR C677T polymorphisms were genotyped by PCR-RFLP. Results: Compared with controls, the plasma Hcy level was significantly higher in the IS patients ( P  < .05). After adjusting for conventional risk factors, the T allele frequency of MTHFR C677T in IS group (54%) was significantly higher than that in the controls (38.3%) ( P  < .05; OR  = 1.890, 95% CI : 1.489–2.399). Additionally, the plasma Hcy level of the TT genotype is significantly higher than that of the CC and CT genotypes ( P  < .05). Conclusion: Our study provided evidence that hyperhomocysteinemia (HHcy) and MTHFR C677T polymorphism were associated with IS. More importantly, suggesting that a possible synergistic effect of MTHFR C677T polymorphism on Hcy level variations increased risk for IS in Chinese population.